PERANAN APARAT KAMPUNG TERHADAP MEMBERDAYAKAN MASYARAKAT DI KAMPUNG WANGGAR MAKMUR DISTRIK WANGGAR KABUPATEN NABIRE - Petrus Mangambe (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
At present the region must conduct its own planning, implementation, and supervision activities. With the increasing workload, human resources must be prepared, both in quantity and quality, meaning that empowerment of the community must be the main priority. Whereas in terms of financing sources, regions are required to be able to finance most activities, so that again creative human resources are needed that can generate thoughts, concepts, and policies. As for the flow of thought in this study, which concerns independent variables namely the role of village officials with the indicators are Coordinator (X1), Motivator (X2) and Communicator (X3). While the dependent variable is Community Empowerment with its indicators are Education (Y1), Economy (Y2), Health (Y3). The role of village officials with three indicators, namely: Facilitator, Motivator, and Communicator. An in-depth study of the role of village officials in community empowerment in a scientific study.